Enhancing Work Engagement: The Role of Interactional Justice and Perceived Organizational Support among Employee - Rizqi Zulfa Qatrunnada; Diah Ayu Saharani; Fachriza Nur Astuty (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to examine the role of interactional justice and perceived organizational support in predicting work engagement among employees in the R&A department at PT X, using a quantitative approach.Methodology: Data were collected through purposive sampling and administered via an online survey distributed through company email. Participants included permanent employees of PT X's R&A Department who had worked at the company for at least one year and were willing to complete the questionnaire in full. The instruments used were the nine-item Interactional Justice Questionnaire, the eight-item Short Version of Perceived Organizational Support (SPOS-8), and the nine-item Utrecht Work Engagement Scale (UWES-9). A total of 67 employees successfully completed the entire survey. Multiple regression analysis was employed to test the research hypotheses.Results: The results revealed that both interactional justice and perceived organizational support significantly influenced work engagement (F = 13.996, p < .001). Specifically, interactional justice (β = .600, t = 3.453, p < .001) and perceived organizational support (β = .361, t = 3.453, p = .028) each had a positive and significant effect on work engagement. Applications/Originality/Value: Therefore, all three hypotheses were supported. The implications of these findings are discussed further in the study.